Evaluation of Physical Activity Profile and Mood State during Ramadan: A study on Sports students - Pramono, Bayu Agung; Priambodo, Anung (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to evaluate the relationship between physical activity and mood stress during the month of Ramadan. A total of 26 college students participated in this study a trial physical activity during Ramadan. Physical activity profiles were measured using the International Physical Activity Questionnaire (IPAQ) and mood profiles using the Profile of Mood States (POMS) in the first and fourth weeks of Ramadan. The results of the analysis showed that sports students tended to maintain a constant level of physical activity throughout the month of Ramadan, absence of significant differences in high-intensity physical activity (vigorous) and moderate between the first and fourth weeks. Although low-intensity physical activity decreased, this change was not significant. In the measurement of POMS components, there was a decrease in the dimensions of depression (DEP), fatigue (FAT), confusion (CON), and vigor (VIG), while the dimensions of tension (TEN) and anger (ANG) increased. In addition, no relationship was found between the IPAQ and POMS profiles in the fourth week, except for the relationship between low-intensity physical activity and Total Mood Disturbance (TMD) scores, which showed a significant positive correlation (r = 0.420, p = 0.033). conclusion, although physical activity tends to be stable during the month of Ramadan, a decrease in low-intensity activity can affect mood stress, indicating the need for managing exercise intensity to maintain psychological well-being. The implications of this study are important for fasting individuals to understand the impact of physical exercise on mental health and consider the appropriate exercise intensity during fasting.